Recurrence of cervical intraepithelial neoplasia at six months post cryotherapy or loop electro-surgical excision procedure at Mbabane Government Hospital Swaziland - Ledibane, N.R.T. (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2018.